ALGORITHM FOR SELECTION OF INDOOR PLANTS TO IMPROVE THE QUALITY OF INDOOR AIR - Новикова, Ирина Игоревна; Чуенко, Наталья Федоровна; Савченко, Олег Андреевич (Medicine in Kuzbass, 2024)
An additional preventive way to improve the indoor air quality, especially in preschool educational organizations (PEO), is the use of indoor plants. The article presents an algorithm of selection (calculation) the indoor plants intended to improve the quality of the air environment depending on the area of the preschool educational organizations, the type of plants, and their leaf apparatus.The purpose of the study is to develop an algorithm for selecting (calculating) the number of indoor plants to improve the quality of the air environment depending on the area of the room, the type of plants, and their leaf apparatus.Material and methods. Based on the results of research and analysis of literature data, plants that are toxic, with thorns and prickles, allergenic and difficult to care for were excluded, and hygienically safe plant species acceptable for use in preschool educational institutions were selected. Hygienic, biological and statistical methods were used. The object of the study were plants selected as a result of our own research and analysis of literature data, acceptable for use in preschool educational institutions. Using biological (measurement of plant parameters) and hygienic (study of microclimate parameters and bacteriological contamination) and statistical methods, a mathematical algorithm for selecting the number of plants was developed.Results. Based on the results obtained, a mathematical algorithm (online calculator) for selecting (calculating) and placing the number of indoor plants intended to improve the quality of the air environment depending on the area of the room, the type of plants, and their leaf apparatus was developed. Examples of the algorithm for calculating the required number of individual plant species to optimize microclimate parameters (relative air humidity) and bacterial contamination of rooms in accordance with hygienic requirements are given.Conclusion. The mathematical algorithm presented in the article for calculating the required number of plants of recommended species taking into account the area of the preschool educational organizations, and the online calculator developed on its basis allows when using them to ensure optimal microclimate parameters and bacterial contamination for indoor premises of preschool educational organizations.
Keywords: children's educational organizations; online calculator; indoor plants; microclimate; transpiration; microbial contamination; improving air quality; closed educational organizations